The influence of age on quality of life after upper body burn. Issue 3 (May 2019) - Santacreu, Eva; Grossi, Laura; Launois, Patricia; López, Silvia; Torrent-Bertran, Maria Lluïsa; Barret, Juan P.
Abstract: Background: In Spain, the number of aged persons is increasing. By the year 2066, it is expected that 34.6% of the Spanish population will be over 65 years of age. Elderly people present a higher burning risk owing in part to impaired balance and decreased physical strength, lower cognitive abilities, or socioeconomic context. Objective: Burns to the upper body body are common and affect both emotional state and physical function, thus leading to reduced quality of life (QoL). Our objective was to determine the influence of age on the QoL of patients who experienced burns to the upper body, with burns with 2 years. Methods: This is an observational study with a sample of 58 patients with burns only on the upper body. Patients were divided into two groups: 29 patients of age over 65 years and 29 patients under 65 years; all of them attended the Vall d'Hebron Burn Center, Barcelona, between 2011 and 2014. From the original sample, 45 patients had survived by the time the information was gathered. The QoL of these individuals was evaluated with the Spanish version of the Burn Specific Health Scale. Demographic data (sex, age, total burn surface area [TBSA], burn mechanism, pathological history, length of hospital stay, and rehabilitation duration) were collected. Statistical analysis included parametric and nonparametric tests as appropriate with R3.3.3. Results: There were no differences between groups regarding the mechanism of burn, TBSA, length of hospital stay, and the domains of QoL test. High blood pressure, diabetes, and other comorbidities were significantly more common in the elderly group than in the younger group. Eleven patients died in the elderly group and two in the younger group (p = 0.012). Conclusion: As opposed to what could be expected, in this study, there were no significant differences between surviving patients in both age groups in terms of perceived QoL. Nevertheless, mortality after a burn in the upper side of the body was significantly higher in elderly people than in younger people. The present study results do not support the use of different rehabilitation approaches in elderly patients.